2016
DOI: 10.3402/qhw.v11.29463
|View full text |Cite
|
Sign up to set email alerts
|

Healthy ageing in Isan-Thai culture—A phenomenographic study based on older persons’ lived experiences

Abstract: Healthy ageing is a concept that concerns older persons’ quality of life and is a key factor in promoting well-being. The older population in Thailand is growing. Isan (a region of north-eastern Thailand) has been reported as having one of the most rapidly increasing older populations in the country. In order to care for and promote the health of older people, healthcare providers should understand how healthy ageing is perceived by this target group. Although healthy ageing has been studied in different conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…Managing late life was related to both economic and emotional aspects. Emotional aspects referred to understanding, acceptance and merit accumulation were similar to the ndings of Manasatchakun [29] that older people in good health viewed death as a natural occurrence to accept and be at peace with when it comes. The current study further found that they trusted merit-making to be a means to safeguard security after death.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Managing late life was related to both economic and emotional aspects. Emotional aspects referred to understanding, acceptance and merit accumulation were similar to the ndings of Manasatchakun [29] that older people in good health viewed death as a natural occurrence to accept and be at peace with when it comes. The current study further found that they trusted merit-making to be a means to safeguard security after death.…”
Section: Discussionsupporting
confidence: 60%
“…Spirituality can likewise be seen as doing good for others driven by internal motivations, but it also results in being accepted by other people in the community. That older persons needed appreciation and respect from children, grandchildren, and friends was also found in Manasatchakun [29]. In late life, they mention having less time to accumulate merit that bene ts current living and the next life.…”
Section: Discussionmentioning
confidence: 79%
“…We selected this province as the setting because it exhibits both rural and urban characteristics and is an example of an area undergoing modernization and growth [ 33 ]. A purposive sampling technique was used to select the participants from a list of family members caring for 17 older persons from 17 families who participated in a previous study on healthy aging in the northeast region of Thailand [ 7 ]. Various background characteristics, such as age, sex, marital status, and educational level, were used as inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of healthy aging is adopted and studied throughout the world [ 5 , 6 ]. In Thailand, studies of healthy aging have focused on older persons' perspectives [ 7 9 ]. The literature indicates that healthy aging is facilitated not only by older persons themselves but also by their families and culture [ 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation